“Others sat murmuring and idle upon the deck”: The Poetics of English Voyage Narratives from the South Sea c. 1700 - Johan HEINSEN (E-REA)
The many English accounts of piracy, privateering and exploration in the South Sea that were produced around 1700 share a language of sea travel. They do so because the narratives themselves were taken to sea and read by other seafarers. Hence, the books themselves travelled and were written with these future voyages in mind. In this regard they read as instructional texts for the constitution of either shipboard authority or scientific observation. In both modes they perform a distancing from the shipboard community and the men among whom they travelled. The discourse that characterized such communities was considered as egalitarian, contentious and/or anarchical. This was the political problem that was to be solved either through a method of incontrovertible observation or a practice of writing that was to aid authoritarian intervention and silencing. In this way, the story of voyaging was to aid the voyage itself. However, reading carefully through the narratives one can also find indications that stories about voyages circulated among the very men whom the voyage narratives portray as idly murmuring. In this way voyage narratives travelled in many guises within the shipboard community itself.